Understanding the Risk Model to the Management Information System of the Supply Chain in the Company's Logistics Process - Dedy Ricardo Serumena; Alb Joko Santoso; B Kristyanto (Journal of Information Systems Engineering and Business Intelligence, 2019)
Background: Various company resources involved in the business become a common commodity that must be used the distinguished is how the management needs manage its information system. Risk Management is one of the arts and sciences in identifying, analyzing, and responding to every risk throughout the product lifecycle.Objective: to investigate the effects of risk management on the performance of the company so they have competitive advantage to maintain their market profits.Methods: We identified and analyzed the weaknesses of one of the Fishing Companies (Pt. Nusantara Fisheries) located in Eastern Indonesia (Ambon) the capital of Maluku province. The approach was carried out by interviewing the highest chair (Branch Head), then 2 administrative and information systems staff, 6 raw material processing company technicians, 4 agents and 16 suppliers from 4 different vessels. The questionnaire was used to find out how important the risk management in the logistics and supply chain so that it found out the risks that were affecting their performance.Results: The results of this approach provided almost 90% of the information needed to analyze the response of this company in the Supply Chain Management conceptual strategy because it had a positive impact on selection, determined the scope of the company, developed a realistic schedule and estimated the right target costs in involving team members to determine strengths and weaknesses in the Supply Chain Process.Conclusion: the companies were able to minimize business failures and the strategy had positive impact.